Banner and Name Board (Case Study in Pangkalpinang City, Bangka Belitung Islands) - Muhammad Iqbal Arrosyad; Asyraf Suryadin; Harun Joko Prayitno (Universitas Muhammadiyah Purwokerto, 2020)
This study aims to explain the forms of fabrik range errors and nameplate in the City of Pangkalpinang, Bangka Belitung Islands and find out the factors behind the occurrence of errors in the use of Indonesian in the fabric range and nameplate in the City of Pangkalpinang, Islands. Bangka Belitung. The method used in this research is qualitative descriptive method. The data collection technique used is the triangulation technique which consists of observation, documentation, and interviews. The subjects in this study were all fabric ranges and nameplate in the city of Pangkalpinang, Bangka Belitung Islands which experienced errors in writing with the use of Indonesian. The results of this study are: the form of class that is often done is in writing sentences in foreign languages, the use of non-standard words, the use of abbreviated words that are not explained, and the use of local languages. and the lack of understanding of the owner of the fabric, the education of the owner or maker cannot be biased because there are still errors even though the education is high through S2, then the purpose of making it does not pay attention to the rules of writing. and almost all spandex fabric or nameplate no one gives input or criticism, it's just that there are some from the public who ask questions related to writing or related businesses.